Structures and dynamics of the subcontinental lithospheric mantle over the central and eastern North American continent, constrained by numerical modeling based on tomography models - Onyebum, Tochukwu Emmanuel (Kansas State University, 2024)
Despite being located within a continental plate, the central and eastern United States (CEUS) has been associated active seismicity, often concentrated along seismic zones such as the New Madrid, the East Tennessee, or the South Carolina Seismic Zones. The influence of mantle convection on the CEUS seismicity is still debated. In this study, we investigate the relationship between mantle dynamics and intraplate seismicity. We do this by modeling mantle convection and the induced tectonic regimes and maximal shear stresses, SHmax, from seismic tomography models. Such an approach has already been used by a few authors, but the results seem to be very sensitive to the parameters of the model, particularly the input tomography models, that depict different structures of the mantle and the lithosphere. In this study, we investigate the sensitivity of the model parameters in reproducing the observed seismicity pattern. The uniqueness of our approach is that we use several global (SEMUCB-WM1, TX2019slab, 3D2018_08Sv, and SL2013Sv) and regional (DNA13, CSEM North America, and CURSA2021) tomography models. Using recent conversion laws, R[subscript [rho]/v], we convert the seismic velocity anomalies provided by tomography models into density anomalies. The density anomalies are then used to compute the instantaneous mantle flow, by considering several rheologies. The modeled convection velocities are used to compute the stress tensor and assess the tectonic regimes and the maximal shear stress, SHmax. Our findings reveal that all the model parameters (i.e., the input tomography models, the conversion factor R[subscript [rho]/v], and viscosity laws) significantly influence the modeled tectonic regimes and SHmax directions, emphasizing the complexity of the problem. However, the SEMUCB-WM1 and TX2019slab global tomography models, provide a better fit to several observed patterns, such as the compression in the northeastern United States, the extension in the Rio Grande Rift and Basin & Range, and the compression reported in most of the seismic zones. The strike-slip deformation evidenced by earthquake focal mechanism in the central US and extension in the region bound by longitudes 257 and 266 degrees remain unexplained by mantle dynamics alone, warranting further investigation regarding alternative causative factors such as Glacial Isostatic Adjustment and Gravitational Potential Energy. Furthermore, our results show that the regional tomography models generally fail to capture observed tectonic regimes in CEUS, suggesting that the seismicity is created by a larger scale mantle flow than the one occurring beneath CEUS.
Keywords: Mantle dynamics; Stresses; Numerical modeling